Eletrossíntese, caracterização e testes de compósitos de polipirrol e poli(DMcT) sobre fibra de carbono como catodos de baterias secundárias e eletrodos de supercapacitores - Davoglio, Rogério Aparecido (Universidade Federal de São Carlos, 2009)
In this work bilayered electrodes made of polypyrrole Ppy and poly(2,5-dimercapto-1,3,4-tiadiazol) poly(DMcT) were produced and characterized on carbon-fiber substrate. To do so, several aspects were investigated: effect of the charge growth (1, 2, 5 and 10 C) on the electrochemical and morphological properties of Ppy electrodeposited on carbon fiber; definition of a growth charge/mass ratio for the Ppy film, leading to a high electrochemical performance electrodes with a stable specific capacity; proposition of an optimized methodology to prepare, by electrochemical means, bilayered composites of Ppy and poly(DMcT) on carbon fiber substrate. All materials had their morphological and electrochemical properties analyzed by means of scanning electron microscopy, cyclic voltammetry and impedance spectroscopy. Thinner Ppy films presented the higher coulombic efficiency and specific capacity values. Electrochemical impedance results indicated that Ppy catalyses the redox reactions of poly(DMcT), allowing its use in secondary batteries. Galvanostatic charge and discharge tests from either thin Ppy film and poly(DMcT)/Ppy (1 C) bilayered film electrodes resulted in excellent performances when used as lithium ion battery cathodes (130 and 300 mA h g-1, respectively) or electrochemical capacitor electrodes (240 and 500 F g-1, respectively).
Electrosynthesis, characterization and tests of polypyrrole and poly(DMcT) composites on carbon fiber as cathodes of secondary batteries and supercapacitor electrodes
Keywords: Físico-química; Polipirrol; Poli (DMcT); Fibra de carbono; Baterias de lítio; Supercapacitores; CIENCIAS EXATAS E DA TERRA::QUIMICA